Physiotherapy Management in a Patient with Coronary Artery Disease 3VD Post Coronary Artery Bypass Grafting in ICCU: A Case Study - Hanidah Aulia Syahma; Tiara Fatmarizka; Purnomo Gani Setiawan; Diani Qomaradewi Indah Sari (Jurnal Kesehatan dan Kedokteran, 2026)
Post-Coronary Artery Bypass Grafting (CABG) patients are at risk of postoperative complications, including pain, respiratory disorders, decreased thoracic expansion, and functional mobility limitations due to surgical procedures and prolonged bed rest in the Intensive Cardiac Care Unit (ICCU). Therefore, physiotherapy during the acute rehabilitation phase is essential to support recovery and prevent further complications. Objective: This study aims to describe physiotherapy management in a patient with Coronary Artery Disease (CAD) three-vessel disease (3VD) post-CABG in the ICCU and to evaluate changes in pain, shortness of breath, thoracic expansion, and functional mobility after physiotherapy intervention. Method: This study used a case report design involving a 53-year-old male patient with complaints of sternotomy pain, shortness of breath, and postoperative mobility limitations. Data were collected through physiotherapy assessment, including vital signs, Numeric Rating Scale (NRS), Borg Scale, thoracic expansion measurement using a meterline, and functional ability using the ICU Mobility Scale. Data were analyzed descriptively by comparing clinical outcomes before and after three physiotherapy sessions. Findings: The results showed decreased resting pain from 5/10 to 3/10, reduced shortness of breath from 2/10 to 0/10, increased thoracic expansion, and improved functional mobility from score 1 to score 3 based on the ICU Mobility Scale. These findings indicate positive clinical progress during the acute rehabilitation phase. Implication: Early physiotherapy intervention through diaphragmatic breathing exercise, deep breathing exercise, active range of motion exercise, and gradual mobilization may support respiratory function, reduce pain, improve mobility, and assist early recovery in post-CABG patients in the ICCU. Originality/Value: This case report provides specific clinical evidence regarding comprehensive physiotherapy management in a CAD 3VD post-CABG patient during intensive cardiac care, particularly through measurable outcomes in the acute rehabilitation phase.